2023
DOI: 10.1038/s41422-023-00887-z
|View full text |Cite
|
Sign up to set email alerts
|

NR5A2 connects zygotic genome activation to the first lineage segregation in totipotent embryos

Fangnong Lai,
Lijia Li,
Xiaoyu Hu
et al.

Abstract: Zygotic genome activation (ZGA) marks the beginning of the embryonic program for a totipotent embryo, which gives rise to the inner cell mass (ICM) where pluripotent epiblast arises, and extraembryonic trophectoderm. However, how ZGA is connected to the first lineage segregation in mammalian embryos remains elusive. Here, we investigated the role of nuclear receptor (NR) transcription factors (TFs), whose motifs are highly enriched and accessible from the 2-cell (2C) to 8-cell (8C) stages in mouse embryos. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…This study showed significant advancements and characteristics in the regulation of CSC activity by the NR5A2 gene [ [46] , [47] , [48] , [49] , [50] ]. First, we used the OCLR algorithm and immune score to fully reveal the expression pattern of NR5A2 in patients with LUAD and systematically elaborated its regulatory mechanism on CSC activity.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed significant advancements and characteristics in the regulation of CSC activity by the NR5A2 gene [ [46] , [47] , [48] , [49] , [50] ]. First, we used the OCLR algorithm and immune score to fully reveal the expression pattern of NR5A2 in patients with LUAD and systematically elaborated its regulatory mechanism on CSC activity.…”
Section: Discussionmentioning
confidence: 99%
“…Nr5a2 and Esrrb together are essential for maintaining naive pluripotency in mouse embryonic stem cells 18 . Recently, Nr5a2 has been identified as a key regulator of zygotic genome activation (ZGA) in murine embryos 19 ( Nr5a2 -knockout embryos have been reported to enter arrest shortly after ZGA 20 , 21 ; however, this could be due to residual maternally deposited Nr5a2 protein in these embryos 19 ). Interestingly, Nr5a2 can replace Oct4 to potently improve the efficiency of induced reprogramming of somatic cells to pluripotency 22 .…”
Section: Mainmentioning
confidence: 99%
“…Their data showed that while Nr5a2 knockdown or knockout did not significantly impact ZGA, it led to impaired activation of 4–8 cell stage genes and resulted in embryonic arrest at the morula stage. Similarly, Festuccia et al reported that Nr5a2 knockout embryos progressed beyond the two-cell stage but exhibited significant developmental delays and morphological abnormalities at the morula stage, highlighting its crucial role in morula development and first lineage specification [ 62 , 63 ]. We hypothesize that further studies using more specific inhibitors targeting Nr5a2 or the same genetic background mice may help resolve the debates about the role of Nr5a2.5.…”
Section: The Role Of Nr5a2 In Zgamentioning
confidence: 99%